Dynamics of particle export on the Northwest Atlantic margin - Hwang, J.; Manganini, S. J.; Montlucon, D. B.; Eglinton, T. I. (Deep-Sea Research Part I-Oceanographic Research Papers, 2009)
The Northwest Atlantic margin is characterized by high biological productivity in shelf and slope surface waters. In addition to carbon supply to underlying sediments, the persistent, intermediate depth nepheloid layers emanating from the continental shelves, and bottom nepheloid layers maintained by strong bottom currents associated with the southward flowing Deep Western Boundary Current (DWBC), provide conduits for export of organic carbon over the margin and/or to the interior ocean. As a part of a project to understand dynamics of particulate organic carbon (POC) cycling in this region, we examined the bulk and molecular properties of time-series sediment trap samples obtained at 968 m, 1976 m, and 2938 m depths from a bottom-tethered mooring on the New England slope (water depth, 2988 m). Frequent occurrences of higher fluxes in deep relative to shallower sediment traps and low Delta C-14 values of sinking POC together provide strong evidence for significant lateral transport of aged organic matter over the margin. Comparison of biogeochemical properties such as aluminum concentration and flux, and iron concentration between samples intercepted at different depths shows that particles collected by the deepest trap had more complex sources than the shallower ones. These data also suggest that at least two modes of lateral transport exist over the New England margin. Based on radiocarbon mass balance, about 30% (+/- 10%) of sinking POC in all sediment traps is estimated to be derived from lateral transport of resuspended sediment. A strong correlation between Delta C-14 values and aluminum concentrations suggests that the aged organic matter is associated with lithogenic particles. Our results suggest that lateral transport of organic matter, particularly that resulting from sediment resuspension, should be considered in addition to vertical supply of organic matter derived from primary production, in order to understand carbon cycling and export over continental margins. (C) 2009 Elsevier Ltd. All rights reserved.
id: 1829; 490AT Times Cited:0 Cited References Count:61Y